Proceedings of the Sixth of International Conference on English Language and Teaching (ICOELT 2018) 2019
DOI: 10.2991/icoelt-18.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Relation in the Quran

Abstract: The language that used in Qur"an is different from the arabian speaker used in their daily life. It is called as classical arabic language. Therefore, translate the Qur"an itself is challenging because many people has their own perception and their analysis in the Qur"an. In addition, many muslims in the world did not speak arabic language so that Qur"an has been translated into many languages but its authentic meaning should be kept. This paper analyse the English translation of Quran. based on the Taxonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…For example, in Surah Al-Baqarah from verse 40-103, the synonymy also can be found. For further text in the Quran, that analyze in the 10 Surah that analyze before by Lubis and Khairuna (2018), synonyme also use to convey the same information but delivered with the different way.…”
Section: Antonymymentioning
confidence: 99%
“…For example, in Surah Al-Baqarah from verse 40-103, the synonymy also can be found. For further text in the Quran, that analyze in the 10 Surah that analyze before by Lubis and Khairuna (2018), synonyme also use to convey the same information but delivered with the different way.…”
Section: Antonymymentioning
confidence: 99%
“…The character development of future generations is a responsibility that all levels and institutions must undertake and carry out (Juharyanto, 2017). Lubis and Khairuna (2019) observed that the coexistence of scientific and non-science issues is one potential notion of an integrated approach and that many researchers have proved the relevance of religion (Lubis & Khairuna, 2019). Religion governs all elements of its adherents' lives as people, members of society, and members of their environment (Djamdjuri & Maeleni, 2021).…”
Section: A Introductionmentioning
confidence: 99%